(untitled) (American Journal of Islam and Society, 2022)
Since the formal end of colonial occupation of African countries by the imperial powers, the last few decades have witnessed ballooning interests in the study of Islam and Muslim societies in especially West Africa. This is partly complimented by the sudden religious transformations and radical shifts from syncretistic strands of Islam brought about by different Islamic reform projects. This factor has posed decisive survival threats to these synctretist groups as the edifices upon which they were initially constructed were being subjected into perpetual checks and cross-examinations. Consequently, the reform projects at times necessitated an internal reexamination within Islamic groups that were hitherto tainted and dominated by traditional practices and beliefs that seem to no longer appeal to scientific and inquisitive minds.